ANALYSIS OF DRUG PROCUREMENT AND PLANNING AT THE PHARMACEUTICAL INSTALLATION OF TOTO KABILA HOSPITAL - Eyaji09, Pransisca (LP2M Universitas Bina Mandiri Gorontalo, 2023)
This study aims to determine whether the process of planning and procurement of drugs at IFRS Toto Kabila has been carried out in accordance with the applicable Standard Operating Procedures. This research method uses descriptive research with a qualitative approach. The study was carried out on 4 informants who were directly related to the planning and procurement process of drugs at the Pharmacy Installation of RSUD Toto Kabila, namely the head of IFRS, head of drug warehouse, pharmacy staff and hospital director by conducting direct interviews with informants with the aim of digging up information related to the planning and procurement process of drugs. The results showed that drug planning at IFRS Toto Kabila was not carried out by a planning team. In this case, the formation of a drug planning team at the Toto Kabila Hospital is not in accordance with the Indonesian Ministry of Health (2010). However, even though the planning was not carried out by a special team based on the results of the interview, the planning was carried out according to the SOP in the hospital and carried out by experts in their fields. Furthermore, in carrying out procurement, IFRS pays attention to the criteria for drug suppliers according to WHO, namely the distance from the PBF location and consideration of the princes offered by the PBF. The conclusion of this study is that drug planning at IFRS Toto Kabila is not in accordance with the Ministry of Health of the Republic of Indonesia (2010) because it is not carried out by a planning team. However, the planning has been carried out according to the existing SOP and carried out by experts in their fields. And also in procuring, IFRS pays attention to the preferences of drug suppliers according to WHO, namely the distance from the PBF location and considers the price offered by the PBF. Then for the budget, you get from 10% -20% of the hospital's income profit every year.